2016
DOI: 10.1371/journal.pone.0151487
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study with Image-Based Rendered Virtual Reality in Patients with Mild Cognitive Impairment and Dementia

Abstract: Virtual Reality (VR) has emerged as a promising tool in many domains of therapy and rehabilitation, and has recently attracted the attention of researchers and clinicians working with elderly people with MCI, Alzheimer’s disease and related disorders. Here we present a study testing the feasibility of using highly realistic image-based rendered VR with patients with MCI and dementia. We designed an attentional task to train selective and sustained attention, and we tested a VR and a paper version of this task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(155 citation statements)
references
References 43 publications
11
134
0
10
Order By: Relevance
“…The same image-based rendering technique was used in an immersive study of people with MCI ( n = 28) and dementia ( n = 29) [24]. Image-based rendering refers to the computerized reconstruction of a real environment, in this case a location familiar to the participants in the city of Nice (France), using a set of photographs.…”
Section: Resultsmentioning
confidence: 99%
“…The same image-based rendering technique was used in an immersive study of people with MCI ( n = 28) and dementia ( n = 29) [24]. Image-based rendering refers to the computerized reconstruction of a real environment, in this case a location familiar to the participants in the city of Nice (France), using a set of photographs.…”
Section: Resultsmentioning
confidence: 99%
“…The motivation level of older adults, which was measured with a homemade questionnaire, was found to be larger for the VR than for the non-VR version of the task, although the difference was non-significant. Using the same motivation questionnaire, Manera et al (2016) reported that older adults with mild cognitive impairment or Alzheimer's disease actually experienced higher levels of satisfaction and security, and lower levels of anxiety, discomfort, and fatigue, during a highly realistic image-based VR cancellation task than during its paper-pencil version . Thus, both studies reported that older adults experience a higher level of motivation for the VR rather than the non-VR version of the same tasks.…”
mentioning
confidence: 99%
“…Type 2 DM starts with insulin opposition, a condition in which cells neglect to react to insulin properly. [2] As the sickness advances, an absence of insulin may likewise develop. This structure was recently alluded to as "non-insulin-subordinate diabetes mellitus" (NIDDM) or "grown-up beginning diabetes".…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…In this way it is critical to duplicate the present outcomes with a greater and progressively adjusted members' example. [2]…”
Section: Virtual Reality In Alzheimer'smentioning
confidence: 99%